Exergy-Based Life Cycle Assessment Model for Evaluating the Environmental Impact of Bridge: Principle and Case Study - Mingjun Ma (MDPI AG, 2021)
The construction of bridge is a complex process and involves diverse energy emission-intensive materials. The evaluation of environmental impacts on the basis of life cycle assessment (LCA) is a recognised technique to find the scope of impact mitigation and save resources. However, the studies on the LCA of bridges are rare and lack assessment on the impact of public transportation during bridge construction. The purpose of this study was to develop an integrated exergy-based LCA model for assessing the environmental sustainability of bridges by investigating their environmental impacts and exergy footprint. The proposed exergy-based LCA model consists of three principal assessment models, namely, the environmental impact of energy consumption, pollutant discharge, and resource consumption. The proposed model was then exemplified with a highway bridge as a case study. The results found that the environmental impact in the raw material production and processing stage was the largest, followed by the construction stage and the operation and maintenance stage at second and third place, respectively. The findings of this study can contribute to mitigating the environmental impacts of bridge construction, and the assessment approach can be adopted to guide the environmental impact evaluation for other types of civil constructions globally.